Democracia, arenas decisórias e políticas públicas: O programa minha casa minha vida - Maria Rita Loureiro; Vinicius Macário; Pedro Guerra (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The present study analyzes the political and institutional arrangements of the new housing program in the Brasil (PMCMV), examining them both from the point of view of democracy and its effectiveness to achieve its objectives. In other words, it aks if such arrangements encourage expanded participation of a plurality of actors and if they favor the coordination of its implementation and the achievement of the goals. The hypothesis considered to be the PMCMV a public policy with institutional arrangement that is politically legitimate and also bureaucratically able for favoring the achievement of the proposed objectives. The selected data, however, showed that this hypothesis has not been completely confirmed. Even having achieved the goals established, with management and monitoring arrangements to raise the efficiency of the policy, its institutional arrangement was not able to include important social actors in the area, such as the popular pró-moradia movements and organized groups of experts on urban themes. their demands have not been addressed in decision-making arenas.
Keywords: O20; Z18; I38; 330; democracy; institutional arrangements; bureaucracy; housing policies